(untitled) (Bangladesh Journal of Medicine, 2023)
The paradoxical response is characterized by clinical or radiologic worsening of pre-existing lesions or the appearance of new lesions following initiation of treatment for tuberculosis (TB). The paradoxical response has raised questions about the accuracy of the diagnosis, the potential for treatment failure, and the presence of an underlying disease, making it an important topic of care for clinicians. In this case report, we present the paradox reaction of a 14 year old girl diagnosed and treated for TB meningitis. This healthy immune girl is successfully treated with steroids, and we discuss the importance of treating the paradox of tuberculosis progression despite the use of effective anti-TB drugs. Bangladesh J Medicine 2023; 34(3): 245-251